2016
DOI: 10.1007/s00259-016-3505-3
|View full text |Cite
|
Sign up to set email alerts
|

18F-alfatide PET/CT may predict short-term outcome of concurrent chemoradiotherapy in patients with advanced non-small cell lung cancer

Abstract: PurposeThe study aims to investigate the role of 18F-alfatide positron emission tomography/computed tomography (PET/CT) in predicting the short-term outcome of concurrent chemoradiotherapy (CCRT) in patients with advanced non-small cell lung cancer (NSCLC).MethodsEighteen patients with advanced NSCLC had undergone 18F-alfatide PET/CT scans before CCRT and PET/CT parameters including maximum and mean standard uptake values (SUVmax/SUVmean), peak standard uptake values (SUVpeak) and tumor volume (TVPET and TVCT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Subsequently, it was further confirmed that changes in 18 F-FPPRGD 2 uptake as early as 1 week after bevacizumab administration may be able to predict the outcome of treatment in patients with cervical and ovarian cancer (21). However, all these results were completely contrary to the results of a previous study (14), which demonstrated that tumor uptake in 18 F-alfatide PET/CT was higher in non-responders than in responders following CCRT. In the present study, the correlation between tumor uptake prior to treatment and the degree of treatment response in the bevacizumab groups was higher than that in the apatinib groups.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Subsequently, it was further confirmed that changes in 18 F-FPPRGD 2 uptake as early as 1 week after bevacizumab administration may be able to predict the outcome of treatment in patients with cervical and ovarian cancer (21). However, all these results were completely contrary to the results of a previous study (14), which demonstrated that tumor uptake in 18 F-alfatide PET/CT was higher in non-responders than in responders following CCRT. In the present study, the correlation between tumor uptake prior to treatment and the degree of treatment response in the bevacizumab groups was higher than that in the apatinib groups.…”
Section: Discussionmentioning
confidence: 80%
“…It is presumed that it is more difficult for chemotherapeutic drugs and oxygen to reach a tumor with increased immature tumor neovascularization. This may be the reason why tumor uptake in 18 F-alfatide PET/CT prior to treatment was higher in non-responders than in responders (P<0.01) (13,14). The negative association between tumor uptake of 18 F-alfatide prior to treatment and the degree of the chemoradiotherapy response may reduce the treatment-response association of bevacizumab to a moderate one in the bevacizumab combined with chemotherapy group.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Seventeen patients with lung cancer were accurately identified among true-negative (hamartoma) as well as false-positive (chronic inflammation and inflammatory pseudotumor) cases. The question of whether 18 F-alfatide PET/CT imaging can predict the short-term outcome of concurrent chemoradiotherapy in patients with advanced non-small cell lung cancer was investigated by Luan et al (26). Responders and nonresponders to chemotherapy could be distinguished with high sensitivity, specificity, and accuracy, confirming that 18 F-alfatide could be a useful tool in therapy response prediction.…”
Section: Silicon-18 F Radiochemistrymentioning
confidence: 99%